THE GOVERNMENT'S ROLE IN HEALTH INSURANCE IN THE PERSPECTIVE OF HUMAN RIGHTS LAW IN INDONESIA - Sri Zanariyah; Ratna Kumala Sari (fakultas hukum universitas PGRI Semarang, 2023)
Human rights are defined as rights attached to human dignity as creatures created by God, and these rights are brought by humans from birth to the face of the earth so that these rights are innate (natural), not a gift from humans or the state. The Indonesian government has provided services in the health sector to the public, by establishing the National Social Security (JSN). The purpose of this research is to find out why health insurance in Indonesia is an activity that can be linked to human rights (HAM) and what is the government's role in implementing health insurance in terms of human rights aspects. The method used in this study is doctrinal (normative) research, so the type of data used is a type of secondary data obtained from literature study. The results of the research can be concluded that the implementation of health insurance follows the social insurance system by providing protection for all people and the government has a role to the implementation of health services based on the principles of humanity, the principle of benefit and the principle of social justice for all people in Indonesia.